EFECTOS DEL LASER Y LOS RAYOS X EN METALES - Monroy C., Oscar S. (2006)
Interaction between solids and two radiations (X-rays and laser) simultaneously is analyzed using non conventional theoretical techniques. In this way, it is calculated induced transition ratio in interbands by X-rays and circular polarized laser with arbitrary intensity. In the case of high moderated intensity laser, it was utilized conventional method of perturbations, so it produced a transition ratio similar to the obtained for Volkov approximation.